Parasites of Marine Fishes off Langkawi, a Preliminary Report - L.H.S, Lim,; W. B, Tan,; K. S, Liew, (Malaysian Journal of Science, 2005)
A preliminary survey on the parasitofauna of marine fishes off Langkawi reveals that in most cases the monogenean species recovered are similar to those from the same fish species caught elsewhere, indicating that locality factors do not affect their distribution patterns. However locality differences do affect the absence or presence of some monogenean species, for example the platycephalids off Langkawi have monogeneans but monogeneans are absent on platycephalids from other areas of Peninsular Malaysia. Hyperparasitism is observed for the first time on Malaysian monogeneans. Some of the fish groups surveyed have not been examined. Descriptions and identifications of these parasites are on-going particularly the gut parasites. Making Langkawi as a national park will enable continuous uninterrupted monitoring to obtain ecological data for health-index and enable investigation of interesting phenomenon such as hyperparasitism